Interleukin-1 Receptor Antagonist (IL-1RN) Gene Variable Number Tandem Repeats (VNTR) Polymorphism Association in men Infertility in Erbil City /Kurdistan Iraq - Yassin Kareem Amin; Ashti M. Said; Ahmed A. Al-Naqshbandi; Saeed Ghulam (مجلة بغداد للعلوم)
The interleukin-1 family has multifaceted roles in men٫s reproductive syste. Out  of these is interleukin-1 receptor antagonist (IL-1RN) which exists in men gonads, and in case of infection and inflammatory process, its activity is increased.  The current study aims to verify a possible linkage of Variable Number Tandem Repeat (VNTR) polymorphism of the IL-1RN gene with human men infertility. The study groups enrolled included 100 infertile men and 100 fertile and healthy men. Their seminal fluids were subjected to analysis. Also peripheral blood samples were collected for the assessment or detection of polymorphic Variable Number  Tandem Repeats (VNTR) polymorphism of interleukin-1 receptor antagonist gene (IL-1RN). Two alleles, namely IL-1RN1 allele corresponding to 410bp fragment and IL-11RN2 that corresponding to 240bp fragments,  are a marker for human men infertility, detected by PCR technique. The results delineated a high frequency of IL-1RN2 allelic gene variants (26%), and two VNTR allelic gene variants carriers IL-1RN1 and IL-1RN2 (16%) among  infertile men with significant impacts on sperm motility and morphology (P< 0.000-0.002) respectively. This prospective study inKurdistan region (Erbil –Iraq)  defined a significant impact of VNTR polymorphism of IL-1RN gene in the etiology of men infertility especially on sperm motility and morphology; particularly carriers of IL-1RN2 allelic variants